Application of AI in Urban Design Education: A Case Study of Master Studio - Heru Wibowo Poerbo; Marisa Sugangga; Elis Anggun Geminastiti; Haryo Winarso; Aswin Indraprastha (DIMENSI: Journal of Architecture and Built Environment, 2026)
This paper explores the transformative potential of AI in urban design studios through a case study where 28 master's students were tasked with simulating an urban design plan for Nusantara - Indonesia's new capital city.  The studio was designed to allow students to engage with each phase of the urban design process using manual techniques, AI-driven tools, or a combination of both, creating a comparative framework to evaluate the advantages and disadvantages of AI in each stage. The goal of this research is to investigate how AI-augmented instruments are being used in educational settings, particularly in creative design courses, and to assess the potential advancements that these tools may offer to the subject. The research further intends to analyse how AI tools affect students' design thinking and technical abilities, leading to strategic recommendations for successfully incorporating these technologies into design education while keep adhering to the ethical guidelines in academic works.